STUDI ELEKTROKIMIA PENGARUH FILM BISMUT DALAM PENENTUAN ARSENIK - SARI, MAYA; Jin, Jiye (IAIN Batusangkar, 2013)
The research objective was to determine arsenic by anodic stripping technique of differential pulse voltammetry to see the effect of the arsenic bismuth films with the potential scan direction opposite to the research that has been done by Nagaosa, et al though there are no reports on the mechanism chemical reaction between arsenic clear with movies bismuth until now. The purpose of this research is to study the effect of bismuth films in the determination of arsenic. In this study, the addition of bismuth ions with a concentration of 200 ppb. Voltammograms can be seen from quite a significant difference between the peak current generated by As (III) films coated with a non-bismuth bismuth films. Visible peak current of As (III) is higher if the addition of bismuth films. This proves the statement Nagaosa, et al who stated that there are mixed effects of bismuth in the determination of As (III) although the mechanism remains unclear.Keyword: film bismuth, arcenic, differential pulse, anodic, stripping voltammetry